Drawing on art : Duchamp and company - Judovitz, Dalia (University of Minnesota Press, 2010)
Marcel Duchamp's 1919 readymade, L.H.O.O.Q., which he created by drawing a moustache and goatee on a commercial reproduction of the Mona Lisa, precipitated a radical reevaluation of the meaning of art, the process of art making, and the role of the artist. This book explores the central importance of appropriation, collaboration, influence, and play in Duchamp's work - and in Dada and Surrealist art more broadly - to show how the concept of art itself became the critical fuel and springboard for questioning art's fundamental premises.